Penerapan Strategi Holywood Square Untuk Meningkatkan Hasil Belajar Tematik Siswa Kelas IV SD Negeri 016 Tambusai Utara - Fatimah, Siti; Khois, Ummu; Rejeki, Rejeki (JURNAL PENDIDIKAN ROKANIA, 2023)
This study aims to find out that th implementation of the Hollywood Squares strategy is to improve the larning outcomes of fourh grand thematic sudents at SD Negeri 016 Tambusai Utara. The background of thid research is that the n0n achievement of the learning objective is reflected in the daily test scores of students in thematic learning from 48 students only 18 students who rach the KKM, while 30 students are doinf remedial activities, the KKM is set at 75. The subjects receiving the action in this study students class IV oda semester 2021/2022 as many as 48 students consisting of 26 female students and 22 male students. The data analysis teachnique used is the model of collecting of collecting several student activity sheets, research, and question sheets. The results of this study werw seen from the first cycle of the first meeting, there were 22 students 46% who reached the KKM. In the first cyle, the second meeting also experienced an increase again, as many as 25 students 58%. In the action of the second cycle of the first meeting, it was known thwt student learning outcomes increased again from 48 students, 30 (63%) students had reached the KKM. At the second meeting, students learning outcomes were very satisfactory, from 48 students (93%). The conclusion of this study is that the implementation of the Hollywood Squares strategy to improve student learning outcomes in the fourth grade thematic learning at SD Negeri 016 Tambusai Utara was successful.